Recreational Style Training for Kindergarten Children and Teachers Based on Canvas Learning Videos and Creative Workbooks to Overcome Impulsive Behaviour in Children - Ramdhani, Lisda; Rahmawan, Ardi; Ramadhan, Puji Laila (Abdi Masyarakat, 2025)
Impulsive and hyperactive behavior in early childhood is a significant challenge in the kindergarten learning process. This condition affects children’s concentration, social interactions, and character development. This community service activity aimed to improve teacher competence and reduce children’s impulsive behavior through recreational-style training based on Canva learning videos and creative workbooks. The methods used included socialization, training, technology implementation, mentoring, evaluation, and program sustainability, involving 13 teachers and 75 students at TK M. Hilir Ismail, Bima City.The pretest–posttest results showed a significant increase in teacher competence, from 25% to 85%, particularly in managing impulsive behavior and utilizing digital media. After the training, all indicators increased, reaching an overall average of 4.25 (85%). In conclusion, recreation-based training with the integration of technology and creative workbooks proved effective in addressing children’s impulsive behavior and enhancing teacher competence. This program has the potential to become an innovative and sustainable learning model for early childhood education, especially in areas with limited educational facilities.